الخصائص العامة للشعر العربي في ولايتي هوسا ويوربا: نظرات مقارنة = General characteristics of Arabic poetry in the Provinces of Hausa and Yoruba: Some comparative considerations = Ciri-ciri umum Syair Arab di Wilayah Hausa dan Yoruba: Beberapa pertimbangan perbandingan - Ahmad H.Osman, Rahmah; Mohammad Jamiu, Abdullahi (IIUM Press, 2015)
مستخلص البحث